(untitled) (Editora Impacto Científico, 2025)
Objective: This study aims to identify the relationship between the epidemiological profile of patients in Brazil’s Unified Health System (SUS) and hospitalizations for burns, length of stay, average cost and mortality rates. Method: Using data from the SUS Hospital Information System (SIH/SUS) from 2008 to 2022, we analyzed hospitalizations, average length of stay, cost and mortality rates due to burns, considering gender, age and ethnicity. Statistical analyses were applied, including ANOVA and post hoc tests. Results: Of the 387,300 cases analyzed, males were more frequently hospitalized, especially in the 1 to 4 year age group. Mortality rates increased with age, being higher in the elderly (80+ years). Ethnic disparities were also observed, with Asians having the highest hospitalization rate and blacks the highest mortality rate. Conclusions: This study highlights the need for specific strategies for different demographic groups in the treatment of burns, including culturally sensitive prevention programs. The disparities identified can guide public health policies to improve outcomes and care in Brazil.